2013
DOI: 10.4012/dmj.2012-186
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of dentin coating materials against abrasion by toothbrush

Abstract: Thin-film coating of root dentin surface by all-in-one adhesives has been shown to be an effective option to prevent root surface caries. The purpose of this study was to investigate the wear resistance against toothbrush abrasion of two all-in-one coating materials; Shield Force (SF) and Hybrid Coat (HC). Bovine dentin surfaces were covered with one of the coating materials; SF or HC. After storage in water for 24 h, the testing surface was subjected to the toothbrush abrasion test up to 50,000 cycles either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Although thermal expansion of such thin layers on flat enamel surface may not be considered as a serious concern, previous studies have suggested that the increased number of thermal cycles accelerated degradation of resin through such mechanisms as increased water sorption and elution of ingredients 36) . Tooth brush abrasion and mechanical wear of resin coatings are also important challenges facing the application of these materials clinically 37) . The demineralization solution in this study was based on previous works, which resulted in formation of a subsurface enamel lesion 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Although thermal expansion of such thin layers on flat enamel surface may not be considered as a serious concern, previous studies have suggested that the increased number of thermal cycles accelerated degradation of resin through such mechanisms as increased water sorption and elution of ingredients 36) . Tooth brush abrasion and mechanical wear of resin coatings are also important challenges facing the application of these materials clinically 37) . The demineralization solution in this study was based on previous works, which resulted in formation of a subsurface enamel lesion 33) .…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities have been proposed for the management of root caries, including the improvement of oral conditions for oral hygiene, topical application of remineralization agents and antimicrobial regimen 6) , and coating or sealing by resin-based materials 7) . However, efficient and simple methods, which can protect the exposed root surface from carious attack for a long term and for elderly patients requiring home care, are not yet currently available 8) . In recent years, a micro-invasive treatment with a low-viscosity resin-infiltrant has become one of the options for non-cavitated enamel caries.…”
Section: Introductionmentioning
confidence: 99%
“…The root dentin surface covered by the application of an adhesive coating material can also prevent bacterial attachment and accumulation 35) . Toothbrush abrasion tests have also demonstrated the excellent durability of thin film coating materials 38) . Thus, the resin-coating technique, when used on the surfaces of exposed roots of older adults and sound teeth, helps not only protect but also reinforce tooth substances (super tooth), thereby promising broader application to preventive dental care in the future.…”
Section: Root Surface Coatingmentioning
confidence: 99%